Barbed wire the fence that changed the West - Liu, Joanne S. (Missoula, Mont. : Mountain Press Pub. Co., 2009)
How the invention of barbed wire transformed the open range of the West into fenced land, creating a violent clash of cultures.
Wide open range -- In the wake of war -- Land up for grabs -- Sticks and stones -- A twist of the wire -- Light as air, stronger than whiskey, cheap as dirt -- The devil's rope -- The fence cutting wars -- Moonshine wire -- Full steam ahead -- The big die-up -- Cattlemen settle down -- Native lands corralled -- Fencing free-for-all -- The new face of the West.
Includes Index and Bibliography
Keywords: Barbed wire -- Social aspects -- West (U.S.) -- History; Barbed wire -- Political aspects -- West (U.S.) -- History; Wire fencing -- West (U.S.) -- History; Frontier and pioneer life -- West (U.S.); Ranch life -- West (U.S.) -- History; Social conflict -- West (U.S.) -- History; West (U.S.) -- History; West (U.S.) -- Social conditions; West (U.S.) -- Race relations